Physical exercise protocols in animal models of Alzheimer's disease: a systematic review - De Sousa, Ricardo Augusto Leoni; Rodrigues, Cintia Maria [UNESP]; Mendes, Bruno Ferreira; Improta-Caria, Alex Cleber; Peixoto, Marco Fabricio Dias; Cassilhas, Ricardo Cardoso (Springer, 2020)
Several animal studies have showed the beneficial effects of physical exercise (PE) on brain function and health. Alzheimer's Disease (AD) is the most common type of dementia, characterized by the presence of aggregated extracellular amyloid-beta (A beta) and neurofibrillary tangles, with progressive cognitive decline. Therapeutic approaches such as PE showed to be effective in halting AD progression. Here, we present a systematic review about PE and AD. The search was carried out using the PubMed and LILACS databases. The following keywords were used: Alzheimer; PE; animal model. All found studies adopted aerobic exercise training as the PE protocol (100%). We identified running on treadmill as the most commonly used PE routine (62.5%). The duration of each session, intensity, frequency, and period of training most used were 60 min/day (62.5%), moderate intensity (87.5%), 5 days/week (62.5%), and 4 (37.5%) or 12 (37.5%) weeks, respectively. The AD animal models most used were the Tg APP/PS1 Delta E9 (25%), models based on i.c.v. infusion of A beta Os (25%) and streptozotocin (25%). All protocols used rodents to their experiments (100%), but mice were the most common (62.5%). Finally, the main results presented in all studies were capable to reduce significantly AD consequences, such as reducing A beta or pro-inflammatory proteins levels (100%). The lack of resistance training protocols in animal models of AD indicates a huge gap that should be investigated in future studies. We suggest that PE protocols must be adapted according to the specie, lineage and life span of the animal.
Keywords: Physical activity; Inflammation; Cognitive decline; Memory; Dementia